Grain loss during winter wheat harvesting (review) - G. A. Filenko; T. I. Firsova; Yu. G. Skvortsova (Зерновое хозяйство России)
Grain loss during winter wheat harvesting (review) Harvesting is an important stage of grain production. It’s necessary to harvest grain crops with a minimum loss and better quality, with a minimum technical and after-harvesting energy costs. Biological direct losses include grain fall from heads, or even the breaking off of the heads, the germination of grain on the root or in the rolls, and finally decrease of the yield from various pests during the harvesting period. The source of biological losses of grain is the harvesting period, including the beginning and duration of harvesting. Mechanical direct losses are losses by roller cutters and pick-ups during a separate harvesting of wheat and losses caused by harvesters (at direct combining). Mechanical losses are the result of grain fall from the head, breaking off the head, leaving non-harvested heads on the field. Winds and rains accelerate the grain fall from the head and sprouting it on the root. Classification of the causes of losses and mechanical damage of grain during combine harvesting show, that all factors are connected with each other. Biological and mechanical direct losses can be equal; one kind of loss can prevail. The grain fall of a variety is a genetically determined complex feature, which depends on the abiotic factors of the environment. That is, the fall of grain directly depends on the weather conditions and varietal characteristics of the head. The grain fall depends on external conditions (air dryness, humidity, etc.) and does not always characterize the resistance of the variety to shedding. This all makes essential to study the dynamics of the formation of traits of resistance to grain fall in varieties of winter soft wheat of different maturing groups and species.